2008
DOI: 10.1080/18125980802633086
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of selected Shona children's songs: Philosophical perspectives on child development

Abstract: Over the years children's songs have been at the core of the physical and cognitive development of a child. They aid in the child's understanding of his social and physical environment and, needless to say, they provide entertainment that helps soothe his or her soul. Indubitably, children's songs have undergone metamorphosis commensurate with the dynamism of life and historical developments. Hence, using an analytical approach, the article seeks to highlight the transformation in children's songs, and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…They addressed how to love God Almighty, fellow humans, parents, brothers and sisters, and the beauty of nature expressed in simple language according to the nature of the children's thinking and can be used to develop ideas, persuade, and educational or moral counsel (Gunawan & Zulaeha, 2017). Therefore, children's songs are cheerful songs reflecting high ethics (Arief & Isnan, 2020;Gunawan & Zulaeha, 2017;Muwati & Mutasa, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They addressed how to love God Almighty, fellow humans, parents, brothers and sisters, and the beauty of nature expressed in simple language according to the nature of the children's thinking and can be used to develop ideas, persuade, and educational or moral counsel (Gunawan & Zulaeha, 2017). Therefore, children's songs are cheerful songs reflecting high ethics (Arief & Isnan, 2020;Gunawan & Zulaeha, 2017;Muwati & Mutasa, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Children's song poetry contains simple things that are usually done by children [20]. Furthermore, according to Muwati, children's songs are songs that are cheerful and reflect high ethics [21]. Based on Kim's opinion, it can be concluded that children's songs teach good things or moral values, or nowadays, it is often called having character education [22].…”
Section: Article Historymentioning
confidence: 99%
“…The lyrics of children's songs are crucial for imparting manners, education, and psychology, evoking emotions through words, vocal gestures, and therefore, are taught frequently in primary school music classes (Satır, 2009). Additionally, Muwati (2008) asserts that children's songs are cheerful and ethically upright. Kim's viewpoint leads us to the conclusion that children's songs impart positive lessons on moral values, or as it is known nowadays, character education (Kim and Kim, 2015).…”
Section: Introductionmentioning
confidence: 99%